2015
DOI: 10.1515/pomr-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Truss Harbor Cranes Modal Design Elements Research

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Signals that are reflected from the previous boundaries of the separation of the two media in the reverse passage of the reflected signal can be ignored based on the following considerations [16,17,18]. As studies have shown in the previous section, the reflection coefficients differ from the transmission coefficients by approximately one order of magnitude and the re-reflected signals, given the attenuation of the signals, will not create any appreciable effect on the total signal.…”
Section: Presenting Main Materialsmentioning
confidence: 99%
“…Signals that are reflected from the previous boundaries of the separation of the two media in the reverse passage of the reflected signal can be ignored based on the following considerations [16,17,18]. As studies have shown in the previous section, the reflection coefficients differ from the transmission coefficients by approximately one order of magnitude and the re-reflected signals, given the attenuation of the signals, will not create any appreciable effect on the total signal.…”
Section: Presenting Main Materialsmentioning
confidence: 99%
“…The effectiveness of the enterprise, measured by economic results, is directly influenced by both downtime of technological devices caused by failure of their components and planned maintenance and reconstruction of the utility (repair) potential [6]. Due to the unforeseen epidemiological situation, many of the transport companies began to generate much higher costs due to the necessity to maintain sanitary requirements, disinfection etc., and to bring lower profits due to the decrease in the number of users [7][8][9]. The number of vehicle kilometers performed in individual quarters in 2019 and 2020 are at a similar level (in 2020 they were enforced by sanitary regulations limiting the number of passengers on public transport).…”
Section: Exploration Processesmentioning
confidence: 99%
“…Resistance to wear of materials is also largely determined by friction processes. In work [10][11][12], the parameters of the friction process in the complex are presented in the model of wear proposed by the authors. The importance of laboratory and theoretical studies of friction parameters for practical applications follows from the literature review.…”
Section: Literature Reviewmentioning
confidence: 99%